Temporal changes in the spatial patterns of air dose rate from 2012 to 2016 at forest floors in Fukushima, Japan. (October 2020) - Imamura, Naohiro; Matsuura, Toshiya; Akama, Akio; Ikeda, Shigeto; Kobayashi, Masahiro; Miura, Satoru; Shinomiya, Yoshiki; Kaneko, Shinji
Abstract: This study investigates temporal changes in the distribution of air dose rates at forest floors from 2012 to 2016 by measuring air dose rates at a height of 10 cm. The study was conducted at four different topography forest sites in Fukushima Prefecture, Japan. At each forest site, the air dose rate was found to have decreased by 7%–22% over time from 2012 to 2016 owing to the movement of radiocesium from organic layers to mineral soil layers in the forest site. However, the spatial distribution patterns of air dose rates did not change at these forest sites over five years. Besides, high correlations between air dose rates and organic plus surface mineral soil inventories were found at these forest sites during most of study years. Therefore, little changes in the spatial distribution of air dose rates could be caused by radiocesium retention at the same location in these forest sites. No statistical correlation between air dose rates and slope gradients was found in the two hilly forest sites with steep slopes above 35°. Accordingly, this study shows that the distribution patterns of air dose rates in the forest floors remained stable depending on the spatial distribution of radiocesium, which formed in the early phase after the Fukushima Daiichi Nuclear Power Plant accident. Highlights: Air dose rate decreased by Cs movement from organic to mineral soil layers. Distribution patterns of air dose rates did not change over five years. Air dose rate correlated with organic plus surface mineral soil inventories. Air dose rates did not correlate with slopes gradients. The distribution pattern was affected by that of Cs formed in the early phase of the FDNPP accident.